2022
DOI: 10.1007/s11325-022-02717-9
|View full text |Cite
|
Sign up to set email alerts
|

Does seasonality affect snoring? A study based on international data from the past decade

Abstract: Background Though snoring is often regarded as a harmless condition that coincides with sound sleep, it is a sleep disorder that can be a potential indicator of more severe conditions such as sleep apnea syndrome. In the present study, we investigated the association between seasonal variations and snoring. Method Search index for snoring (SIS) data were obtained from Google Trends and Baidu Index. SIS data were collected for the USA, India, Germany, Russi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 53 publications
0
2
0
Order By: Relevance
“…Research by Masna et al emphasized that other factors, such as the thermal season, can also impact adenoid mucus [23]. This observation was also stated by Wang et al, who showed seasonal dependence of snoring problems related to nasal blockage in the general population [36]. A reduction in nasal resistance plays an important role in reducing snoring [37].…”
Section: Discussionmentioning
confidence: 83%
“…Research by Masna et al emphasized that other factors, such as the thermal season, can also impact adenoid mucus [23]. This observation was also stated by Wang et al, who showed seasonal dependence of snoring problems related to nasal blockage in the general population [36]. A reduction in nasal resistance plays an important role in reducing snoring [37].…”
Section: Discussionmentioning
confidence: 83%
“…With the rapid development of Internet technology, long-term and continuous data collection based on the Internet has brought opportunities for disease prediction and early warning, especially for COVID-19 ( 20 , 22 ). According to China's Internet Network Information Center (CNNIC), from 2017 to 2019, the average usage rate of search engines in all types of Internet applications was 82.12%, and the brand penetration rate of the Baidu search engine was 90.9%, showing it has become an important window for Chinese citizens to obtain information.…”
Section: Methodsmentioning
confidence: 99%
“…Because of the rise of the Internet and the advancement of Internet technology, it is now possible to investigate the prevalence of asthma. Previous research on snoring in China, the United States, Russia, and India using the Baidu Index and Google Index revealed that snoring varies with the seasons ( 20 ). We investigated the prevalence of asthma in China using China's Health Statistics Yearbook and searches about “asthma” using the Baidu index.…”
Section: Introductionmentioning
confidence: 99%